THEORY AND PRACTICE OF THE CHARACTERISTIC LOCUS DESIGN METHOD. - Kouvaritakis, B (1979)
Recent work on the application of complex-variable theory to the analysis of linear multivariable systems has led to a design philosophy that integrates the frequency-response and the root-locus approach. A discussion of the 2-stage design technique that derives from this philosophy is undertaken, and its application to a 3-input/3-output model of a once-through boiler is considered. On the face of lack of excess measurements an outer-loop design study only is carried out where frequency-response techniques are employed for the adjustment of the open-loop characteristic properties of the system. Through the use of the approximately commutative controller, it is shown that it is possible to gain/phase compensate the system characteristic gain using classical lead/lag and proportional plus integral controllers. The overall control scheme results in a system whose response is fast, nonoscillatory, accurate in the steady state and largely nonovershooting and noninteractive.